The Effect of Advertisements and Consumer Reviews on Buying Interest in Wardah Cosmetic Products in Medan City with Social Media Involvement as a Moderation Variable - Mey Ramayanti Tinambunan; Dwi Sakinah; Lamriama Valintina Chrystina Siregar; Syafrizal Helmi Situmorang (International Journal Business, Management and Innovation Review, 2024)
Using social media engagement as a moderating variable, this research seeks to assess the impact of advertising and user reviews on purchasing interest in cosmetic items in Medan City. The data was gathered from 130 participants who filled out a survey using a Likert scale. To assess the link between variables, Partial Least Squares Structural Equation Modeling (PLS-SEM) is utilized for analysis. Both advertisements and customer reviews significantly impact consumers' propensity to make a purchase, while the former has a stronger impact. However, social media engagement has not been proven to moderate the relationship between advertising and consumer reviews and buying interest. This model successfully explains 98.1% of the variance of buying interest, which shows the high power of the model in predicting consumer buying interest. Based on these results, marketing strategies that focus on advertising and consumer reviews need to be optimized to increase consumer buying interest.